Access to alternative donor hematopoietic search and transplantation for acute leukemia in different macro-regions of Italy. A GITMO/IBMDR study. (March 2018) - Milone, Giuseppe; Sacchi, Nicoletta; Gallina, Anna; Leotta, Salvatore; Picardi, Alessandra; Guidi, Stefano; Tripepi, Giovanni; Rambaldi, Alessandro; Bonifazi, Francesca
Abstract Hematopoietic Stem Cell Transplantation activity levels vary across European countries. No data are available on the homogeneity of access to the transplant procedure for patient with leukaemia, within any European country. We measured homogeneity of the rate of alternative donor search in patients affected by acute leukaemia resident in each Italian region and macro-region during years 2010–2013. A total of 2747 alternative donor searches were studied. Twenty-one percent of all donor searches were made through extra-regional migration. Rate of alternative donor searches varied among the country's regions and macro-regions. The rate of donor searches was 38% lower in South Italy than in North Italy, and the rate of alternative donor transplantations performed was 45% lower. A reduced rate of alternative donor search in South macro-region was observed in all age cohorts. Despite the overall allogeneic transplant rate in Italy is relatively high, there are wide regional differences in access to transplant from alternative donor. Extra-regional migration cannot completely compensate for the lower access to transplant of acute leukaemia patients living in those regions where transplant activity is low.